Implementing data hiding in still images / lman Hazwam Abd. Halim and Roshidi Din - Abd. Halim, lman Hazwam; Din, Roshidi (2004)
Data hiding refers to the nearly invisible embedding of information within various host data sets and one of them is by using still images. It is a highly multidisciplinary field that combines image and signal processing with cryptography, communication theory, coding theory, signal compression, and the theory of visual perception. There are a number of ways exist to hide information in still images. Common approaches include least significant bit insertion, masking and filtering, algorithm and transformations, and spread spectrum techniques. Each of these techniques can be applied, with varying degrees of success, to different image files formats. The data hiding process of each method will be discussed in this paper and the comparison tables that. show the suitability of different image file types with the recent data hiding methods according to some parameters also will be provided. This paper also will discuss about the challenges in implementing data hiding in still images.